Product market deregulation and the US employment miracle - Monique Ebell; Christian Haefke (Institute for Advanced Studies (IHS), 2008)
We consider the dynamic relationship between product market entry regulation and equilibrium unemployment. The main theoretical contribution is combining a job matching model with monopolistic competition in the goods market and individual bargaining. We calibrate the model to US data and perform a policy experiment to assess whether the decrease in trend unemployment during the 1980's and 1990's could be directly attributed to product market deregulation. Under a traditional calibration, our results suggest that a decrease of less than two-tenths of a percentage point of unemployment rates can be attributed to product market deregulation, a surprisingly small amount. Under a small surplus calibration, however, product market deregulation can account for the entire decline in US trend unemployment over the 1980's and 1990's.
Keywords: E24; J63; L16; O00; 330; product market competition; barriers to entry; wage bargaining; Gesamtwirtschaftliche Produktion; Marktstruktur; Monopolistischer Wettbewerb; Deregulierung; Arbeitsmarkt; Beschäftigung; USA